Aluminum tris(dihydrogen phosphate) [Al(H2PO4)3] as an efficient and heterogeneous catalyst for the environmentally friendly preparation of N,N'-alkylidene biscarbamates - Shafiee, Mohammad Reza Mohammad; Zakaria, Mohamad Pauzi; Azar, Parviz Aberomand (IEEE, 2010)
A tri-component reaction of phenyl acetylene/1-Hexyne, aromatic aldehyde and benzyl/methyl carbamate. Aluminum tris(dihydrogen phosphate) [Al(H2PO4)3] has been described to establish different kinds N,N'-alkylidene biscarbamates. The corresponding N,N'-alkylidene biscarbamates have been obtained in good to excellent yields. The prepared catalysts were characterized by X-ray diffraction. The products were obtained with high conversion and yields.